Community Perception Regarding the Performance of the Village Head in Botubilotahu Village, Marisa District, Pohuwato Regency - Edy Sijaya; Hasman Umuri (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2023)
The purpose of this study was to find out how the perceptions and views of the community regarding the performance of the village head in the village of botubilotahu, sub-district of marisa, district of pohuwato. The method in this research is descriptive with a qualitative approach to make descriptive, descriptions or paintings in a systematic, factual and accurate way about facts, characteristics in relation to phenomenal relationships that are the focus of research. The results showed that based on the results of research and findings in the field related to public perceptions of the performance of the village head of botubilotahu as measured through the quality dimension, it can be concluded that from the four questions in the indicator, the average perception of respondents was GOOD based on the calculation of the respondent's answer interval scale. Based on the results of research from the responses and perceptions of the community about the performance of the village head of botubilotahu which is presented through the frequency table above which is correlated with the findings of the researchers in the field, then overall that the quantity indicator, it can be concluded from the three questions in the indicator that the average perception is LESS GOOD from respondents based on the calculation of the respondent's answer interval scale. Based on the results of research from the responses and perceptions of the community about the performance of the village head of botubilotahu which is presented through the frequency table above which is correlated with the findings of the researchers in the field, relating to indicators of the implementation of the village head's duties, it can be concluded from the three questions in the indicator that the average perception is LESS GOOD of respondents based on the calculation of the respondent's answer interval scale. Based on the results of research from the responses and perceptions of the community about the performance of the village head of botubilotahu which is presented through the frequency table above which is correlated with the findings of researchers in the field, relating to the Responsibility indicator, it can be concluded from the three questions in the indicator that on average they get a GOOD perception from respondents based on calculation of the respondent's answer interval scale.